Estimation of Parameters in Tank Models Analysis From a Discharged Simulation in Sibundong Hydropower - Lufira, Rahmah Dara; Marsudi, Suwanto; Haribwowo, Riyanto; Sajali, Muhammad Amar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2022)
In the planning of hydroelectric power plant requires sufficient discharge data for the purpose of hydrology analysis of the watershed. With the tank model, it is expected to be able to perform a discharge simulation to find out the amount of discharge in the river. The purposes of this study are to apply the tank model in the estimation of river discharge and calculate the dependable discharge on the Sibundong river, in addition, it is also to analyze the potential power of Sibundong hydropower. From the result of the generator discharge analysis, it can be analyzed the probability of discharge reliability based on Flow Duration Curve that is Q = 9.29 m3/s, P = 60 %. The power potential that can be generated for the hydro power operation pattern is 2 x 6.26 MW and the energy is 1,489.96 GWh/year.